THE EFFECT OF WORK STRESS ON NURSE PERFORMANCE IN THE INPATIENT WARDS TANJUNG PURA HOSPITAL ON 2016 - Nopa, Ika; Zulfendri, Zulfendri; Fauzi, Fauzi (Buletin Farmatera, 2020)
Nursing care in a hospital is an integral part of health service. A nurse has constant contact with patients within 24 hours, and her work demands can potentially cause stress. The main purpose of the research was to find out the influence of work stress on nurses' performance in the Inpatient Wards.The research was a survey with an explanatory research method to find out the influence of work stress on nurses' performance in the Inpatient Wards of RSUD (Regional General Hospital) Tanjung Pura. The population was 63 nurses in the Inpatient Wards, and all of them were used as the samples since their numbers were relatively small. The data were gathered by conducting in-depth interviews and reporting data were obtained from the hospital. The gathered data were analyzed by using a linear regression statistic test.The result of the research showed that 77.8% of the respondents had moderate performance, 14.3% of the respondents had a good performance, and 7.9% of the respondents had a bad performance. It was also found that the variable of work stress influenced the performance at p-value = 0.00001.It is recommended that the hospital management pay attention to the nurses? condition in each Inpatient Ward. On the other hand, the hospital management should give special attention to the work stress undergone by the nurses in the Inpatient Wards